BANK AKTIVLARI SAMARADORLIGI VA TAHLILI - Tadjiyeva Eleonora Shavkatovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article covers the issues of efficiency and analysis of bank assets. The purpose of the study is to study the theoretical and practical aspects of assessing and analyzing the effectiveness of bank assets. Scientific literature analysis, statistical processing and comparison methods have been used as research methods. The results show that the effectiveness of bank assets is an important indicator of the functioning of the bank, and its assessment and analysis are important in ensuring the financial stability of the bank. The results of the study can be used in the development of recommendations for improving the effectiveness of bank assets.